Cephalic heterochronies in domestic rabbits: A first study - Parés-Casanova, Pere M. (2020)
Heterochrony is defined as the evolutionary changes in the timing of development, presenting a unified view of neoteny, recapitulation, paedogenesis, retardation, progenesis, etc. In order to detect processes of heterochrony and differentiate them, 291 fresh corpses of domestic rabbits of different purposes ("belier" type n=73, "toy" type n=112, meat type n=71) were studied, from which facial and cephalic lengths were obtained, and compared them with 35 wild rabbits (Oryctolagus cuniculus). The regression lines of facial length versus the cranial length appeared homogeneous among types, but slopes showed statistically different values and, in all cases, allometric coefficients exceeding 1. This would be interpreted as a clear expression of hypomorphoses for toy rabbits (slope was lower than that for wilds), but hypermorphosis for meat animals (slope was higher than that for wilds). Wild rabbit, on the other hand, presented a development with a sudden stop, due to their lower body weight and hence shorter cephalic growth.